Work engagement dan employee wellbeing pada dosen - Afrianti, Lidia; Rahmi, Tuti; Febriani, Utari (Jurnal Riset Psikologi, 2023)
Abstract: contribution of work engagement to employee wellbeing of state university lecturers. The purpose of this study was to determine the contribution of work engagement to employee wellbeing in state university lecturers in Indonesia. This study used a quantitative method with cluster sampling techniques and tested by normality test, linearity test, and linear regression analysis. The sample of this research was 107 state university lecturers. The results of the study show that there is a positive contribution between work engagement and employee wellbeing in state university lecturers.Abstrak: kontribusi work engagement terhadap employee wellbeing dosen perguruan tinggi negeri. Tujuan penelitian ini adalah untuk mengetahui kontribusi work engagement terhadap employee wellbeing pada dosen perguruan tinggi negeri di Indonesia. Penelitian ini menggunakan metode kuantitatif dengan teknik pengambilan sampel cluster sampling dan diuji dengan uji normalitas, uji linieritas, serta analisis regresi linear. sampel penelitian ini berjumlah 107 orang dosen perguruan tinggi negeri. Hasil penelitian menunjukkan bahwa terdapat kontribusi positif antara work engagement dan employee wellbeing pada dosen perguruan tinggi negeri.